Analysis of Cellulose and Cellulose Acetate Production Stages from Oil Palm Empty Fruit Bunch (OPEFB) and Its Application to Bioplastics - Hanifah, Aisyah; Mardawati, Efri; Rosalinda, S; Nurliasari, Desy; Kastaman, Roni (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2022)
Oil Palm Empty Fruit Bunch (OPEFB) is a type of solid waste from the palm oil processing industry. The components of OPEFB include cellulose, hemicellulose, and lignin. OPEFB has a large cellulose content, so it possesses the potential to be used as a bioplastic material. The purpose of this research was to examine the stages of the bioplastics' production process and its characterization. The cellulose content of OPEFB as raw material and during the isolation process which includes hydrolysis, delignification, pulping, and bleaching are 39.59%, 56.00%, 59.85%, 61.48%, and 68.20%, respectively. Cellulose isolation produces α-cellulose content of 97.87%. The resulting cellulose acetate has an acetyl content of 25.93%. The bioplastics were then characterized to determine the effect of cellulose acetate, starch, chitosan, and glycerol on the physical and mechanical properties of the plastics. The results of the physical properties characterization include biodegradability, water absorption, and density with values of 78.73%, 38.26%, and 1.2% respectively. The results of the mechanical properties characterization include tensile strength, elongation, and modulus of elasticity with values of 0.729 MPa, 4.13%, and 17.5 MPa, respectively. The functional groups in the bioplastics, which are O-H, C-H, C-O, C=O, and N-H, are produced from the mixing process between cellulose acetate, starch, chitosan, and glycerol.